Implementasi Kurikulum dalam Pembelajaran di SD Darul Ma’arif Numbay - Sunjayani Allyuwava Kurnywa; Diva Amilia Ramadhani; Al Dewiyana Muhammad Idris; Didik Efendi (Journal of Creative Student Research, 2026)
This study aims to describe the implementation of the curriculum in learning at Darul Ma'arif Elementary School. This research is motivated by the importance of the curriculum as a guideline in organizing education to achieve learning objectives effectively and directed. The study uses a qualitative approach with a descriptive type. The research subjects consisted of class teachers and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while the validity of the data was tested through technical triangulation. The results of the study indicate that the implementation of the curriculum was carried out through the stages of planning, implementation, and evaluation of learning. Teachers have prepared learning tools according to learning outcomes. The dominant methods used are lectures, questions and answers, and giving assignments. In general, the implementation of the curriculum has gone quite well, but still needs improvement in the variety of learning methods and the application of authentic assessments so that educational objectives are achieved optimally.